Dietary total antioxidant capacity in early school age and subsequent allergic disease. Issue 6 (14th March 2017) - Gref, A.; Rautiainen, S.; Gruzieva, O.; Håkansson, N.; Kull, I.; Pershagen, G.; Wickman, M.; Wolk, A.; Melén, E.; Bergström, A.
Summary: Background: Dietary antioxidant intake has been hypothesized to influence the development of allergic diseases; however, few prospective studies have investigated this association. Objective: Our aim was to study the association between total antioxidant capacity (TAC) of the diet at age 8 years and the subsequent development of asthma, rhinitis and sensitization to inhalant allergens between 8 and 16 years, and to assess potential effect modification by known risk factors. Methods: A total of 2359 children from the Swedish birth cohort BAMSE were included. Dietary TAC at age 8 years was estimated by combining information on the child's diet the past 12 months from a food frequency questionnaire with a database of common foods analysed with the oxygen radical absorbance capacity method. Classification of asthma and rhinitis was based on questionnaires, and serum IgE antibodies were measured at 8 and 16 years. Results: A statistically significant inverse association was observed between TAC of the diet and incident sensitization to inhalant allergens (adjusted odds ratio: 0.73, 95% confidence interval: 0.55–0.97 for the third compared to the first tertile, P ‐value for trend = 0.031). Effect modification by traffic‐related air pollution exposure was observed, with a stronger association between dietary TAC and sensitization among children with low traffic‐related air pollution exposure ( P ‐value for interaction = 0.029). There was no evidence for effect modification by GSTP1 or TNF genotypes, although these results should be interpreted with caution. No clear associations were observed between TAC and development of rhinitis or asthma, although a significant inverse association was observed for allergic asthma (ORadj 0.57, 95% CI 0.34–0.94). Conclusions and Clinical Relevance: Higher TAC of the diet in early school age may decrease the risk of developing sensitization to inhalant allergens from childhood to adolescence. These findings indicate that implementing an antioxidant‐rich diet in childhood may contribute to the prevention of allergic disease.